Model Prediksi Kebutuhan Air Berbasis Sistem Dinamik di Kabupaten Mojokerto - Asmorowati, Erna Tri; Sarasanty, Diah (Universitas Riau, 2021)
Mojokerto is one of the leading regions in East Java Province This of course has consequences for growth in all fields, especially industry and housing. So that it will have an influence either directly or indirectly on the growth of other supporting facilities growth in various fields leads to increased demand for water due to climate change, several springs in Mojokerto district have decreased by 60% from their original condition. This study aims to predict future water needs with the influence of changes in population, the effect of increasing the number of industries and facilities, both commercial and non-commercial using a dynamic system so that it can be used as a basis for water resource management decisions. In analyzing a complex system that works with real conditions, it is very risky and costly, therefore we need a model that can represent the conditions of the existing system. The stages in the research are as follows: 1. Secondary data collection in the study area which includes: Population data, data on the number of public facilities, data on the number of hotel rooms, data on the number of hospital rooms, data on rice fields, data on the number of livestock, data on the area of tourism and data on the number of markets; (2) Data Analysis; (3) System Dynamic Analysis;(4)Simulation of water demand prediction in the study area;(5) Model validation with the structure validation test and the AVE and AME validation tests. The simulation model for the prediction of water demand in Mojekerto Regency based on a dynamic system is declared valid because it has fulfilled the structure test and validation test both AVE and AME From the results of the scenario simulation applied, it was able to save water by 30% for domestic water needs and 92% for non-domestic water needs. It is necessary to make a model to determine the availability of existing water resources so that a model of water resources balance in Mojokerto Regency is compiled.